Kepemimpinan Kharismatik K.H. Muhammad Djunaid Sulaiman Dalam Mengembangkan Pendidikan Islam Di Kabupaten Bone - Mujahidil Muhajirah (El-Idare, 2019)
This article discusses "The Charismatic leadership of K.H. Muhammad Djunaid Sulaiman in developing Islamic education in Bone regency". This type of research is used qualitatively with historical, sociological, and phenomenological approaches. The data source of this research is scholars literacy (biography of K.H. Muhammad Djunaid Sulaiman), family, students of K.H. Muhammad Djunaid Sulaiman and head master of Islamic schoul. Further, the method of data collection is historical observation, interview, and dicumentation. Then, the technique of data processing and analizing is done through three stages, they are data reduction, data presentation and conclude. The fidings slows that the charismatic leadership value of K.H. Muhammada Djunaid Sulaiaman in developing Islamic Education in Bone Regency, like that value of Ada Tongeng, Getteng, Sabbara, Siri, and Lempu. Has ingrained in himself as Pattola Palallo generation of royal and religious descent. Starting from establishing an boarding schools, presenting citation, his way to criticize the government, until motivating people, cannot be separated from his charismatic value. Ethis and aesfhetics in this movement presents polaritation of Ada na Gau (according to words and deeds) which is become as strong foundation in building collective awareness of Bone people. The efforts to develop Islamic education in Bone makes him work without expecting a penny.